Multi-Tissue Acceleration of the Mitochondrial Phosphoenolpyruvate Cycle Improves Whole-Body Metabolic Health - Abulizi, Abudukadier; Cardone, Rebecca L.; Stark, Romana; Lewandowski, Sophie L.; Zhao, Xiaojian; Hillion, Joelle; Ma, Lingjun; Sehgal, Raghav; Alves, Tiago C.; Thomas, Craig; Kung, Charles; Wang, Bei; et al. (Cell metabolism, 2020)
The mitochondrial GTP (mtGTP)-dependent phosphoenolpyruvate (PEP) cycle couples mitochondrial PEPCK (PCK2) to pyruvate kinase (PK) in the liver and pancreatic islets to regulate glucose homeostasis. Here, small molecule PK activators accelerated the PEP cycle to improve islet function, as well as metabolic homeostasis, in preclinical rodent models of diabetes. In contrast, treatment with a PK activator did not improve insulin secretion in pck2−/− mice. Unlike other clinical secretagogues, PK activation enhanced insulin secretion but also had higher insulin content and markers of differentiation. In addition to improving insulin secretion, acute PK activation short-circuited gluconeogenesis to reduce endogenous glucose production while accelerating red blood cell glucose turnover. Four-week delivery of a PK activator in vivo remodeled PK phosphorylation, reduced liver fat, and improved hepatic and peripheral insulin sensitivity in HFD-fed rats. These data provide a preclinical rationale for PK activation to accelerate the PEP cycle to improve metabolic homeostasis and insulin sensitivity. [Display omitted] •Pyruvate kinase activators (PKa) amplify insulin release in preclinical T2DM models•PKa amplify insulin release via the phosphoenolpyruvate cycle in vivo•PKa acutely short-circuit gluconeogenesis and accelerate red blood cell glycolysis•PKa improve insulin sensitivity, steatosis, and dyslipidemia in obese rats Abulizi et al. show that small molecule activation of mitochondrial PEPCK (pck2)-dependent phosphoenolpyruvate (PEP) cycling amplifies glucose-stimulated insulin secretion without evidence of islet injury and improves insulin sensitivity in vivo. These are accompanied by decreased gluconeogenesis, increased red blood cell glycolysis, and reduced hepatic steatosis in preclinical rodent models of diabetes.